1996
DOI: 10.1143/jjap.35.l793
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Single Crystal Fiber Growth by Micro Pulling Down Method

Abstract: Silicon single crystal fibers with a constant diameter as small as 200 µ m have been successfully grown by the micro pulling down technique. Grown crystal fibers are uniform in shape and contain a large defect-free volume. Basic parameters for stable growth were discussed in association with the conservation of mass and heat as well as the meniscus stability of the molten zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 3 publications
1
15
0
1
Order By: Relevance
“…Crystalline silicon (Si) fibers were first reported in 1996 and were grown by the micro-pull-down method [97]. Perhaps ahead of their time, such fibers did not generate much attention until a decade later when high-pressure chemical vapor deposition (HP-CVD) was employed to realize silicon inside the open capillaries of a silica (SiO 2 ) photonic crystal fiber [98].…”
Section: Semiconductor Core Optical Fibersmentioning
confidence: 99%
“…Crystalline silicon (Si) fibers were first reported in 1996 and were grown by the micro-pull-down method [97]. Perhaps ahead of their time, such fibers did not generate much attention until a decade later when high-pressure chemical vapor deposition (HP-CVD) was employed to realize silicon inside the open capillaries of a silica (SiO 2 ) photonic crystal fiber [98].…”
Section: Semiconductor Core Optical Fibersmentioning
confidence: 99%
“…They also found that the axial temperature gradient near the crystal/melt interface remains very high during a stable operation, between 473 and 573 K/mm. Since then, fibers of many materials have been grown using the m-PD method including silicon [14], silicon germanium [15], lead tungstate [16], terbium aluminum garnet [17], optical oxides [18][19][20][21][22][23], sapphire [24,25], and fluorides [26][27][28]. As found in all these experimental investigations, the m-PD method allowed for high pull rates and good axial homogeneity of crystals.…”
Section: Introductionmentioning
confidence: 95%
“…There are several methods for growing fiber crystals [4]. The micro-pulling down (μ-PD) process, a variant of the inverse edge-defined film-fed growth, developed by Fukuda's laboratory in Japan [5][6][7][8][9], has been promising in producing single crystal fibers with good diameter control and concentration uniformity.…”
Section: Introductionmentioning
confidence: 99%